2023
DOI: 10.1093/molbev/msad106
|View full text |Cite
|
Sign up to set email alerts
|

CAGEE: Computational Analysis of Gene Expression Evolution

Abstract: Despite the increasing abundance of whole transcriptome data, few methods are available to analyze global gene expression across phylogenies. Here, we present a new software package (CAGEE) for inferring patterns of increases and decreases in gene expression across a phylogenetic tree, as well as the rate at which these changes occur. In contrast to previous methods that treat each gene independently, CAGEE can calculate genome-wide rates of gene expression, along with ancestral states for each gene. The stati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Specifically, we leverage single-cell full-length RNA sequencing data to investigate the role of selection on gene expression and function in subclonal evolution of cancer. We model clonal gene expression evolution using stochastic Ornstein-Uhlenbeck (OU) processes which have been previously applied in the context of species evolution 17,18,19,20,21,22,13 and cellular differentiation 11 , but have not been utilized in studies on subclonal evolution. Our use of OU processes allows us to model changes in subclone-specific expression along trajectories defined by the evolutionary history of the subclones.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we leverage single-cell full-length RNA sequencing data to investigate the role of selection on gene expression and function in subclonal evolution of cancer. We model clonal gene expression evolution using stochastic Ornstein-Uhlenbeck (OU) processes which have been previously applied in the context of species evolution 17,18,19,20,21,22,13 and cellular differentiation 11 , but have not been utilized in studies on subclonal evolution. Our use of OU processes allows us to model changes in subclone-specific expression along trajectories defined by the evolutionary history of the subclones.…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption may (Dimayacyac et al 2023) or may not (Hahn and Nakhleh 2016a) be the best strategy. On the other hand, modeling evolution as a function of a particular gene tree may prove beneficial for traits predicted to exhibit a more direct one-to-one correspondence with a single tree, such as expression of a gene largely regulated by cis elements near its encoded locus (Chen et al 2019;Bertram et al 2022;Bastide et al 2023;Dimayacyac et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps such scenarios arguably represent a best case in which we might at least hope to match tree with trait. Fitting PCMs to gene expression data has also garnered recent considerable interest for modeling functional genomic evolution across cells, tissues, and species (Chen et al 2019;Bertram et al 2022;Adams et al 2023;Bastide et al 2023;Dimayacyac et al 2023). Somewhat surprisingly, a recent study found that modeling gene expression as a function of the overall species tree improved the fit of Ornstein-Uhlenbeck models (Dimayacyac et al 2023), even when compared to local gene trees.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to controlling for unobserved (and phylogenetically structured) confounding variables, phylogenetic comparative methods (PCMs; for reviews of these methods see Pennell and Harmon 2013 ; Harmon 2019 ) are increasingly being used to characterize the evolutionary dynamics of gene expression over time, for example, by looking for the signature of selection in the distribution of gene expression values at the tips ( Oakley et al 2005 ; Bedford and Hartl 2009 ; Brawand et al 2011 ; Dunn et al 2013 ; Rohlfs et al 2014 ; Rohlfs and Nielsen 2015 ; Price et al 2022 ). And accordingly, there have been a number of recent methodological developments, including computational platforms for simulating ( Bastide et al 2023 ) and analyzing ( Bertram et al 2023 ) phylogenetic comparative gene expression datasets.…”
Section: Introductionmentioning
confidence: 99%